A GTPase distinct from Ran is involved in nuclear protein import (The Rockefeller University Press, 1996)
Signal-dependent transport of proteins into the nucleus is a multi-step process mediated by nuclear pore complexes and cytosolic transport factors. One of the cytosolic factors, Ran, is the only GTPase that has a characterized role in the nuclear import pathway. We have used a mutant form of Ran with altered nucleotide binding specificity to investigate whether any other GTPases are involved in nuclear protein import. D125N Ran (XTP-Ran) binds specifically to xanthosine triphosphate (XTP) and has a greatly reduced affinity for GTP, so it is no longer sensitive to inhibition by nonhydrolyzable analogues of GTP such as guanosine 5'-O-(3-thiotriphosphate) (GTP gamma S). using in vitro transport assays, we have found that nuclear import supported by XTP-Ran is nevertheless inhibited by the addition of non-hydrolyzable GTP analogues. This in conjunction with the properties of the inhibitory effect indicates that at least one additional GTPase is involved in the import process. Initial characterization suggests that the inhibited GTPase plays a direct role in protein import and could be a component of the nuclear pore complex.